Translation and psychometric evaluation of the Persian version of the nurses' quality of life scale: a validation study in Iran - Mehrdad Yousefnezhad; Habib Shareinia; Elahe Lal Kheirkhah; Moosa Sajjadi (BMC, 2024)
Abstract Background The quality of life for nurses can be significantly impacted by various occupational factors that Influence their working conditions and professional performance. The current study aimed to translate and validate the Persian version of the Nurses' Quality of Life Scale. Material and method In this cross-sectional research, the Nurses' Quality of Life Scale (NQOLS) was utilized to assess the quality of life among 500 employed nurses in hospitals in the cities of Gonabad and Sabzevar. The translation process of the NQOLS followed the model proposed by Wild et al. The content validity of the Persian version of the scale was evaluated using the Content Validity Index (CVI) and Content Validity Ratio (CVR). Structural validity was assessed using exploratory and confirmatory factor analyses. Internal consistency reliability was assessed using Cronbach's alpha, while test-retest reliability was determined using the Intraclass Correlation Coefficient (ICC). Data analysis was conducted using SPSS version 26 and LISREL version 8.8 software. Results The exploratory factor analysis of the Persian version of NQOLS revealed six factors that accounted for 62.15% of the total variance. The structural validity of the extracted factors was confirmed through confirmatory factor analysis. The Cronbach's alpha coefficient and ICC for the entire questionnaire were 0.91 and 0.95, respectively. Conclusion The findings of the present study suggest that the Persian version of the NQOLS exhibits sufficient validity and reliability. Therefore, it can be used as an effective tool for measuring and examining the quality of life among nurses in Iran.